2015
DOI: 10.1016/j.yrtph.2015.02.015
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the validity and applicable domain of the toxic load model: Impact of concentration vs. time profile on inhalation lethality of hydrogen cyanide

Abstract: Sweeney, Lisa M.; Summerville, Douglas R.; Channel, Stephen R.; Sharits, Brian C.; Gargas, Nathan M.; and Gut Jr., Chester P., "Evaluating the validity and applicable domain of the toxic load model: Impact of concentration vs. time profile on inhalation lethality of hydrogen cyanide" (2015). In the present investigation, experiments were conducted to extend the evaluation of the applicable domain of the model for acute lethality of HCN in the rat (cumulative exposure range of 2900-11,000 ppm min). The lethali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…The validity of the toxic load models for extrapolation from constant exposures to time-varying exposures is being tested by comparing outcomes from rat studies with standard (constant) profiles with outcomes from studies where rats are exposed to time varying concentrations. In a previous series of experiments using hydrogen cyanide (HCN), we concluded that as long as continuous exposures lasted 5 min or longer, the toxic load model was consistent with the outcomes of variable-concentration exposures with and without gaps (brief [30% of total duration] periods with no exposure) (Sweeney et al, 2014(Sweeney et al, , 2015. No definite conclusions could be made about the toxic load model concerning shorter exposures (less than 5 min) due to probable breath-holding on the part of the rats.…”
Section: Introductionmentioning
confidence: 71%
See 4 more Smart Citations
“…The validity of the toxic load models for extrapolation from constant exposures to time-varying exposures is being tested by comparing outcomes from rat studies with standard (constant) profiles with outcomes from studies where rats are exposed to time varying concentrations. In a previous series of experiments using hydrogen cyanide (HCN), we concluded that as long as continuous exposures lasted 5 min or longer, the toxic load model was consistent with the outcomes of variable-concentration exposures with and without gaps (brief [30% of total duration] periods with no exposure) (Sweeney et al, 2014(Sweeney et al, , 2015. No definite conclusions could be made about the toxic load model concerning shorter exposures (less than 5 min) due to probable breath-holding on the part of the rats.…”
Section: Introductionmentioning
confidence: 71%
“…As noted above, the current experiments and analyses build off of previous efforts in which HCN was used as the test chemical (Sweeney et al, 2014(Sweeney et al, , 2015. The current effort was a departure from the previous efforts in that a different test chemical was used.…”
Section: Selection Of Test Chemicalmentioning
confidence: 99%
See 3 more Smart Citations